“HUMAN, HUMANITY, AND HUMANITIES” DALAM PENCIPTAAN KARYA KRIYA KULIT - Rohmad Eko Priyono (Institut Seni Indonesia Yogyakarta, 2017)
The creation of it has a title “human, humanity, and humanities” The author would like to learn about the unique symbol of a Human and its application in the form of the installation of art. The approach used in the creation is an aesthetic approach, the method used is based on the aesthetic values embodied in art. Aesthetic is the main objective in the creation of works derived from the shape of a Human. Terms of design that has been studied in the study of art as craft unconscious part spontaneously out of the standard values in making the creation of craft art, starting from sketches to the final stage. Semiotics is used in the creation of works of art craft is semiotics Charles Sanders Peirce - sign approach based on the idea of a philosopher and thinker United clever, Charles Sanders Peirce (1839-1914) is the method used to determine whether a work of art has meaning symbol, index, and icon. This approach is actually used as the meaning of the meaning and purpose of the philosophical. In this case, the artist commented aesthetic value and his symbolization, artists explore the beauty, the uniqueness of the shape of a human and then pour it into the leather craft three-dimensional and two-dimensional. And artists have chosen the concept of human as a concept in leather craft work.Keyword: Creation, Craft, Leather and the Making Process Jurnal Penciptaan ini memiliki judul